The woods Protophyllocladoxylon and Metapodocarpoxylon within the Cretaceous terrestrial biota of northern Africa. (October 2021) - El-Noamani, Zainab M.; El-Saadawi, Wagieh E.; Philippe, Marc
Abstract: New tracheidoxyls from near the Protophyllocladoxylon leuchsii Kräusel type-locality (El-Kharga, Egypt, Turonian) were xylologically studied. Although most of the samples are not identifiable, one has preserved features, in particular araucarian radial pitting and co-occurrence of podocarpoid and oopores in the cross-fields, which allow assignment to Metapodocarpoxylon libanoticum (Edwards) Dupéron-Laudoueneix et D. Pons. This is the first time that this taxon has been formally recognised among samples from near this location. This sample, a topotype for P. leuchsii, is pivotal in demonstrating that P. leuchsii is a taxonomical synonym of M. libanoticum . This reinforces a recently published nomenclatural proposal to conserve the name Protophyllocladoxylon with a conserved type. It also suggests that, paradoxically as its first type was from Egypt, the genus Protophyllocladoxylon is missing from northern Africa terrestrial biota during the Cretaceous. There, conversely, an endemic vegetation flourished, linked to the large alluvial plains, dominated by Agathoxylon - and Metapodocarpoxylon -trees and which might have been the Angiosperm cradle. Highlights: For the first time tracheidoxyls from the Protophyllocladoxylon leuchsii Kräusel type-locality were xylologically studied. The present topotype for P. leuchsii confirms that P. leuchsii is a taxonomical synonym of Metapodocarpoxylon libanoticum . This finding reinforces a recently published proposal to conserve the name Protophyllocladoxylon with a conserved type. This study proves that genus Protophyllocladoxylon is missing from northern Africa terrestrial biota during the Cretaceous.